Pengaruh Penerapan Strategi Pembelajaran Active Learning Tipe Guided Teaching Terhadap Hasil Belajar Akidah Akhlak Di MAN 2 Payakumbuh - Aliah Syahira. Z; Supriadi Supriadi; Charles Charles; Jasmienti Jasmienti (Universitas Pahlawan Tuanku Tambusai, 2022)
The background of the problem in this study is the learning process at MAN 2 Payakumbuh in the Akidah Akhlak lesson seen still using the lecture method. This can be seen from the low learning outcomes of students. This is due to various factors, one of which is teacher-centered learning. In the teaching and learning process students often only listen and take notes on the material presented by the teacher. This results in students being less active and less involved in the learning process. To overcome this problem, the author applies the learning strategy of Active Learning Type Guided Teaching in the learning process. The purpose of this study was to determine the effect of the Guided Teaching Type Active Learning learning strategy on the learning outcomes of Akidah Akhlak students of class XI IPK at MAN 2 Payakumbuh. The method used in this research is quantitative with the type of Quasy Experimental Design. The population in this study were all students of class XI IPK at MAN 2 Payakumbuh as many as three classes, all of which were normally distributed and had homogeneous variants. Because all of them are normally distributed and have homogeneous variants, the authors took the initiative to choose XI IPK 1 and XI IPK 3 as samples. Based on the results of the analysis and discussion of the research data, the hypothesis results obtained by t-test, t count = 9,399 and t table = 1,998, then t count > t table so that Ho is rejected. Based on these results, it can be concluded that, there is an effect of the application of Active Learning type guided teaching on the learning outcomes of Akidah Akhlak at MAN 2 Payakumbuh. Keywords: Learning, Active Learning, Guided Teaching